One: CENTRO TECNOLÓGICO SAN JOAQUÍN. - Plaut, Jeannette (Architectural Record, 2007)
The article features the Centro Technolóogico San Joaquin in Santiago, Chile. The building, commissioned for one of the campuses of the renowned Portificia Unibersidad Catóolica de Chile, is designed to contain computer equipment and laboratories for the campus, and is intended to accommodate 500 students. Fundamentals of the design are provided.